2016
DOI: 10.1128/cvi.00564-15
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte Perturbations in Malawian Children with Severe and Uncomplicated Malaria

Abstract: Lymphocytes are implicated in immunity and pathogenesis of severe malaria. Since lymphocyte subsets vary with age, assessment of their contribution to different etiologies can be difficult. We immunophenotyped peripheral blood from Malawian children presenting with cerebral malaria, severe malarial anemia, and uncomplicated malaria (n = 113) and healthy aparasitemic children (n = 42) in Blantyre, Malawi, and investigated lymphocyte subset counts, activation, and memory status. Children with cerebral malaria we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
45
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(57 citation statements)
references
References 29 publications
10
45
1
1
Order By: Relevance
“…We report high plasma levels of proinflammatory cytokines and chemokines (IFNγ, TNF, IL-6, CCL2, CCL3, CCL4, CXCL10) in severe malaria patients compared to baseline uninfected follow-up, which matched that of Py infection in mice in which we could conduct a temporal analysis. Only few studies have performed functional immunophenotyping during severe human malaria [21, 25], and most of them focused on specific subsets of immune cells, namely NK cells, γδT cells and CD4 + T cells. Our study examined both myeloid and lymphoid cell compartments to provide a global analysis of blood immune leukocytes during severe human malaria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We report high plasma levels of proinflammatory cytokines and chemokines (IFNγ, TNF, IL-6, CCL2, CCL3, CCL4, CXCL10) in severe malaria patients compared to baseline uninfected follow-up, which matched that of Py infection in mice in which we could conduct a temporal analysis. Only few studies have performed functional immunophenotyping during severe human malaria [21, 25], and most of them focused on specific subsets of immune cells, namely NK cells, γδT cells and CD4 + T cells. Our study examined both myeloid and lymphoid cell compartments to provide a global analysis of blood immune leukocytes during severe human malaria.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, a role for Foxp3 + CD4 + regulatory T cells (Tregs) as well as non-Foxp3 + activated/memory (CD45RO + ) CD4 + T cells in regulating malaria-induced inflammation and subsequent immunopathology is supported by many studies in human patients and in surrogate mouse models [1924]. NK and γδ T cell activation is increased in children suffering from CM compared to other forms of malaria, as is the proportion of activated/memory T cells [25]. Inflammatory CCR2 + CD14 + monocytes mediate antibody-dependent cellular inhibition, and their higher proportion was correlated to lower blood parasitemia in acute uncomplicated malaria patients [9].…”
Section: Introductionmentioning
confidence: 99%
“…Antibodies that develop through exposure to P. falciparum play a role (3), and the involvement of different lymphocyte subsets has been implicated in both protection against, and pathogenesis of, malaria (46). …”
Section: Introductionmentioning
confidence: 99%
“…Triplicate Results from flow cytometric analysis unexpectedly revealed that 46.9% (mean, n = 15) of these CD8 mid cells expressed the prototypic NK cell maker, CD56 ( S1 Fig, cell population 9) . Abnormal lymphocyte subtypes have been previously reported in patients from malaria endemic areas [10, 36]; however, at the time of writing, this phenotype has not been reported in Haiti to the best of our knowledge, and may be unique to the study population. Both CD8 mid populations (CD56 + and CD56 - ) experienced a statistically significant rise in the percentage of positive cells in the asymptomatic patient group exposed to infected erythrocytes at the schizont stage (iRBC lysate) vs uninfected erythrocytes (uRBCs; Fig 4A and 4B).…”
Section: Resultsmentioning
confidence: 80%